THE PHENOMENON OF RETRACTION IN THE POETRY OF THE POET SULTAN AL-SABHAN- DIWAN (COLLECTION) OF (OTHER DETAILS OF WATER) AS A "MODEL" PUBLISHED ON AL-SHAER ONLINE BLOG - Nawal Abdullah Ebrahim Alzahrani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Blog is a website that collects a number of posts and is like a diary or a forum for giving personal opinions. The blog is an application of the Internet, in which blogs are written to convey news or express ideas, and it works through a content management system, which in its simplest form is a web page on the Internet on which notes (entries) are dated and arranged in ascending chronological order of which a number is published A specific one controlled by the blog's director or publisher, and the system includes a mechanism for archiving old entries, and each of them has a permanent path that does not change from the moment it is published that enables the reader to return to a specific post at a later time when it is no longer available on the first page of the blog, and also ensures the stability of the links And inhibits its decomposition. This paper stands with the aspects of retraction of the poet: Sultan Al-Sabhan, through his book "Other Details of Water", published on the poet's electronic blog, after introducing retraction language and idiom, and also introducing the poet: the author of the divan. This study is based on the stylistic approach that deals with looking at the phenomenon and its retraction. The research has been divided into an introduction, a topic and a conclusion. As for the introduction, it includes two axes, the first of which is concerned with the term retraction in the lexical and idiomatic lexicon, and the other concerned with the definition of the poet and his poetry, then the topic comes to stand on the structural retraction in the Diwan (collection) in three styles, in the methods of presentation, Objection, and deletion, and then the conclusion is a summary of the most important research results.